POLITIK HUKUM PEMILIHAN METODE KONVERSI SUARA MENJADI KURSI DALAM SISTEM PEMILIHAN UMUM LEGISLATIF TAHUN 2019 DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 7 TAHUN 2017 TENTANG PEMILIHAN UMUM - Erna Hasibuan; Mexsasai Indra; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In general election contestation, the election of the method of converting votes into seats often gets less attention in election arrangements. In fact, the difference in the type of vote conversion method used will also affect the difference in the number of seats that can be obtained by a political party in parliament. In the history of elections in Indonesia, there are at least two types of vote conversion methods that have been used, namely the Hare Quota method and the Divisor Sainte-Lague method. The purpose of writing this thesis: first, to find out whether the method of converting votes into seats in the 2019 Legislative General Election system in Indonesia is in accordance with the principles of General Elections based on Law Number 7 of 2017. Second, to find out how the Legal Politics of Use the Sainte Lague method in Law Number 7 of 2017 concerning General Elections.This research is a normative juridical research, research conducted based on legal materials and legislation. The approach taken includes a library approach, namely by studying books and laws and regulations. The types of data used are primary data types, secondary data sources, namely data sources derived from books and other regulations. The theory used in this research is the theory of legal politics and the theory of the general election system.From the results of the study there are two main things that can be concluded. First, the method of converting votes into seats in the 2019 Legislative General Election system in Indonesia can be said to be inconsistent with the principles of the General Election Law Number 7 of 2017. There are several points that cause this to be inconsistent, including: (1) the method This is not considered effective when implemented. (2) this method creates the potential for the formation of new parties that take advantage of the situation. (3) by using this method of converting votes into seats, it will create a sense of injustice for a handful of political parties in navigating the election contestation. Keywords: Political Law-Voice Conversion Method-General ElectionLegislative-Law Number 7 Year 2017